Optimized watermarking technique using self-adaptive differential evolution based on redundant discrete wavelet transform and singular value decomposition. (30th December 2018) - Vali, Mohammad Hassan; Aghagolzadeh, Ali; Baleghi, Yasser
Highlights: The proposed method satisfies all of the watermarking requirements simultaneously. Scaling factors are optimized using self-adaptive differential evolution algorithm. Fitness function assures a pre-defined imperceptibility while maximizing robustness. A verification process is prepared to solve the false positive problem. Abstract: Imperceptibility, capacity, robustness and security are four basic requirements of any watermarking technique. A new blind image watermarking technique based on the redundant discrete wavelet transform (RDWT) and singular value decomposition (SVD) is presented in this paper to satisfy all of these four watermarking requirements simultaneously. The gray-scale watermark image is directly embedded into the singular values of RDWT sub-bands after multiplying by a scaling factor. The self-adaptive differential evolution (SADE) algorithm is used to optimize the scaling factor values with the aim of reaching the highest possible robustness while guaranteeing a pre-determined watermarked image quality. By the use of human visual system (HVS) characteristics, an 8-bits digital signature is inserted into the watermarked image to solve the false positive problem which is a prevalent security problem for the most SVD-based watermarking methods. The digital signature is used for verification test before initialization of the watermark extraction procedure. Also, considering the existing redundancy in the RDWT domain, the scheme attained a large amount of capacity. Experimental results demonstrate that in addition to achieving a great imperceptibility, large capacity and sufficient security, the proposed scheme obtains a satisfactory level of robustness against image processing and geometrical attacks, simultaneously.